2002
DOI: 10.1002/1521-3765(20020902)8:17<4037::aid-chem4037>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

The Di-Iron Subsite of All-Iron Hydrogenase: Mechanism of Cyanation of a Synthetic {2Fe3S}–Carbonyl Assembly

Abstract: This paper describes the kinetics and intimate mechanisms associated with cyanation of {2Fe3S} assemblies to give species structurally related to the subsite of all‐iron hydrogenase. Stopped‐flow FTIR spectroscopy has enabled the quantitation of the dynamics of five well‐defined steps that experimentally illustrate the role of bridging carbonyls in the assembly of the dicyanide species, how on–off sulfur ligation can have a dramatic effect on cyanation kinetics and how the {2Fe3S} core stabilises bridging carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
75
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 9 publications
6
75
0
Order By: Relevance
“…In contrast, the second cyanation step of the {2Fe3S} species is kinetically slower than for the {2Fe2S} monocyanide because one of the Fe atoms is deactivated by the coordination of the electron-donating thioether group. It also turned out that the intermediate species formed in the second cyanation step of {2Fe3S} species is a μ-CO species, confirming the structural assignment made on the basis of FT-IR data [153]. In a wider context, the study provides some insight into the reactivity of dinuclear systems in which neighbouring group on-off coordination can play a role in substitution pathways [154].…”
Section: Quantum Mechanical Methods In Bioinorganic Chemistry: the Acsupporting
confidence: 77%
“…In contrast, the second cyanation step of the {2Fe3S} species is kinetically slower than for the {2Fe2S} monocyanide because one of the Fe atoms is deactivated by the coordination of the electron-donating thioether group. It also turned out that the intermediate species formed in the second cyanation step of {2Fe3S} species is a μ-CO species, confirming the structural assignment made on the basis of FT-IR data [153]. In a wider context, the study provides some insight into the reactivity of dinuclear systems in which neighbouring group on-off coordination can play a role in substitution pathways [154].…”
Section: Quantum Mechanical Methods In Bioinorganic Chemistry: the Acsupporting
confidence: 77%
“…Deprotonation of the pendant phenol led to a species possessing an infrared spectral profile similar to those of other diiron pentacarbonyl complexes reported previously [3,5,8,20]. Infrared spectroscopic analysis, tandem mass spectrometric, and theoretical investigations suggested that this species with an Fe I -OR bond, [Fe 2 (μ-SCH 2 ) 2 CMe(CH 2 -o-C 6 H 4 O)(CO) 5 ] − (1), takes the geometry found for other neutral diiron pentacarbonyl complexes reported in the literatures [5,6].…”
supporting
confidence: 75%
“…8 The final product showed characteristic spectral pattern of diiron pentacarbonyl complexes [3,5,8,20]. Plotting the average absorption bands of those diiron pentacarbonyl complexes reported in literatures against those corresponding bands of the proposed complex 1 produces an excellent linear correlation, Fig.…”
mentioning
confidence: 74%
“…Pickett and coworkers thoroughly explored the chemistry of first-generation Fe 2 S 3 models, which feature coordination of a pendant thioether sulfur (RSR) to one of the iron centers [233][234][235][236][237][238]. Complexes synthesized by Pickett, Song and their respective coworkers feature coordination of an external iron-bound thiolate ligand to one of the iron centers of the Fe 2 S 2 (CO) 5 core [231,239].…”
Section: [Fefe]h 2 Asementioning
confidence: 99%